2017
DOI: 10.1007/s00213-016-4518-0
|View full text |Cite
|
Sign up to set email alerts
|

Bibi ergo sum: the effects of a placebo and contextual alcohol cues on motivation to drink alcohol

Abstract: RationaleAcute ‘priming’ doses of alcohol reliably increase alcohol-seeking behaviour in social drinkers. However, the effects of the anticipated (rather than pharmacological) effects of alcohol, and their interaction with contextual alcohol cues, are not well understood.ObjectivesThis study aims to determine the extent to which an alcohol-placebo drink increases craving, subjective intoxication and beer consumption, while conjointly investigating the impact of contextual alcohol cues.MethodsOn a within-subjec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
17
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 41 publications
2
17
0
Order By: Relevance
“…Study 1 replicated previous research, showing that initial alcohol consumption can increase (prime) alcohol-seeking [ 2 5 , 16 , 17 ]]. However, ad lib beer consumption did not differ between alcohol and placebo sessions within study 2, although, craving was higher in the alcohol sessions.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…Study 1 replicated previous research, showing that initial alcohol consumption can increase (prime) alcohol-seeking [ 2 5 , 16 , 17 ]]. However, ad lib beer consumption did not differ between alcohol and placebo sessions within study 2, although, craving was higher in the alcohol sessions.…”
Section: Discussionsupporting
confidence: 81%
“…Consistent with previous work [e.g. 17 , 18 ] the light-headedness scale of the SIS was used as the primary measure of subjective intoxication ( Table 2 ). A 2 x 2 x 3 mixed ANOVA with condition (average-control, high-control) as a between-subject variable and drink (alcohol, placebo) and time (baseline, post-drink and end of session) as within-subject variables revealed there to be a significant drink x time interaction, F (2, 158) = 75.95, p < .001, η p 2 = .49.…”
Section: Study 1: Resultsmentioning
confidence: 99%
“…In other words, it is suggested that alcohol consumption may, at times, be associated with behaviour change not through intoxication itself but via beliefs and expectancies regarding the effects of intoxication. As such, anticipated effects from consuming an alcohol placebo resulting in behavioural changes may be observed (in line with perceived normative attitudes and behaviour), that are akin to those that may be expected when alcohol is actually consumed (Christiansen et al, 2017). Indeed, in support of this contention, recent research has found placebo alcohol to increase craving, ad libitum alcohol consumption, subjective intoxication (Christiansen et al, 2017), disinhibition, and indirectly, outcome expectancies (Christiansen et al, 2016).…”
Section: Alcohol Administration Protocolmentioning
confidence: 88%
“…Firstly, the current study did not include a pure control beverage condition, when participants are aware that they are not consuming alcohol. The anticipated effects of alcohol from a placebo appear to increase alcohol craving and further alcohol consumption above that of a pure control (Christiansen et al, 2017). It may therefore be that a lack of alcohol effect on mood change is in part due to the anticipated effects of alcohol.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation